Development of a Brazilian standard procedure for in vitro digestion using rumen fermenters - Camacho, Larissa Frota (2021)
This thesis aimed to propose a standard Brazilian procedure for evaluating the in vitro dry matter digestibility (IVDMD) for ruminant feeds using artificial fermenters and a machine- rinsing procedure for filter bags after in vitro digestion. To recommend a machine-rinsing procedure were used twenty aliquots of for different feeds (Tifton 85 hay, corn silage, soybean meal and soybean hull) incubated in an artificial rumen fermenter for 48 hours. Then, the filter bags were rinsed in a washing machine for seven 1-min cycles. The undigested residues did not decrease (P>0.05) from third rinse. The variance among replicates also stabilized from third rinse. We concluded that a minimal of three 1-min cycles of machine rinsing are recommended for ruminal in vitro assays using filter bags, which provides stabilized apparently undigested residues and minimized variance among replicates. To propose a standard procedure for IVDMD, a collaborative study was performed with seven Brazilian feed-analysis laboratories and same samples used on machine-rinsing procedure. Two artificial fermenters were evaluated: Daisy II Ankom and TE-150 Tecnal. Each one of the laboratories received 80 sealed filter bags with samples (20 per feed), eight blank filter bags, a plastic bag with buffer solution’s reagents and instructions describing how to conduct a 48-h in vitro assay using an artificial fermenter and how to collect bovine ruminal inoculum. On average, the contribution of laboratory effect for the total random variance was 24%, being lesser than the contribution of equipment (42%) and random error (34%). The repeatability varied from 3.34 to 5.79% across feeds. The reproducibility varied from 5.93 to 8.94% across feeds, which implied in Horwitz ratios varying from 2.94 to 4.10. Due to specific characteristics of the evaluated analytical entity (i.e., IVDMD), which is defined by the method itself, the prosed method was considered reproducible. In summary, the results highlighted that, if the method is followed exactly recommended, its results are precise and present adequate levels of repeatability and reproducibility. Keywords: Collaborative study. Horwitz ratio. In vitro digestibility. Rinsing procedure. Thesis.